The rate of change is gonna be 0
First you are going to look at the smallest box and figure out what the area is once you do that you will need to find the area of the bigger box once you figure out both of the areas you will then find out what they are you will then add up the amounts to get the area of both squares together
Area = length *width
A = x²
3x² = (x+10)(x+12)
3x² = x²+10x+12x+120
3x² = x²+22x+120
3x²-3x² = x²+22x+120-3x²
0 = -2x²+22x+120
Factor to solve for x:
-2(x²-11x-60)
(x+4)(x-15)
x = -4 & x = 15 but we can't have a negative length so we eliminate 4. The length of the square is 15 cm.
Answer:
C:) 17/3
Step-by-step explanation:
Simplify the following:
((3 + 2/5)×5)/3
((3 + 2/5)×5)/3 = ((3 + 2/5)×5)/3:
((3 + 2/5)×5)/3
Put 3 + 2/5 over the common denominator 5. 3 + 2/5 = (5×3)/5 + 2/5:
((5×3)/5 + 2/5 5)/3
5×3 = 15:
((15/5 + 2/5)×5)/3
15/5 + 2/5 = (15 + 2)/5:
((15 + 2)/5×5)/3
15 + 2 = 17:
(17/5×5)/3
17/5×5 = (17×5)/5:
((17×5)/5)/3
((17×5)/5)/3 = (17×5)/(5×3):
(17×5)/(5×3)
(17×5)/(5×3) = 5/5×17/3 = 17/3:
Answer: 17/3